Schizophyllum Commune a Causative Agent of Fungal Sinusitis: A Case Report - T. Premamalini; B. T. Ambujavalli; S. Anitha; L. Somu; Anupma J. Kindo (Case Reports in Infectious Diseases)
We present a case of maxillary sinusitis caused by Schizophyllum commune, in a 50-year-old female. The patient presented with nasal obstruction, purulent nasal discharge from right side of the nose, cough, headache, and sneezing. Computed tomography revealed extensive opacity of the right maxillary sinus as well as erosion of the nasal wall and maxillary bone. Functional endoscopic sinus surgery was done, and fungal debris present on right side of the maxillary sinus was removed and sent to laboratory. Potassium hydroxide (KOH) examination of the nasal discharge showed hyaline, septate hyphae. Primary isolation on Sabouraud's dextrose agar (SDA) yielded a white woolly mould. Banana peel culture after 8 weeks showed macroscopically visible fan-shaped fruiting bodies. Lactophenol cotton blue (LPCB) mount of the same revealed hyaline septate hyphae, often with clamp connections. Identification was confirmed by the presence of clamp connections formed on the hyphae and by vegetative compatibility with known isolates.